TRANSFORMASI EKONOMI GLOBAL MELALUI PRINSIP KEADILAN EKONOMI ISLAM DALAM MENGATASI KEMISKINAN - puspa utami (LA RIBA: Jurnal Perbankan Syariah, 2025)
This study aims to analyze the implementation of justice principles in Islamic economics as a transformative effort to address global poverty and social inequality. Islamic economics emerges as an alternative paradigm that emphasizes justice, balance, and sustainability contrasting with capitalist and socialist systems that often lead to inequality and structural as well as moral crises. This research employs a library research method with a descriptive and analytical approach through the review of academic literature, scholarly journals, and research reports on the application of Islamic economic principles in various countries. The findings indicate that key instruments such as zakat, waqf, and the prohibition of riba play a strategic role in achieving equitable wealth distribution, reducing poverty, and strengthening social solidarity. Moreover, the Islamic financial system based on profit-and-loss sharing and ethical business practices encourages economic stability that is more resilient and sustainable in the face of global crises. Major challenges in its implementation include the dominance of global capitalism, low levels of Islamic economic literacy, and limited regulatory and technological support. Nevertheless, through the integration of Islamic ethical values, technological innovation, and international collaboration, Islamic economics has the potential to serve as a foundation for a more inclusive, stable, and human-centered global economic system.